Women Participation and Role of Co-Operative in Financial Inclusion of the Women Inside Pokhara Metropolis - Lamichhane, Baburam (KIC International Journal of Social Science and Management, 2023)
Co-Operatives are economic entity; they deliver the opportunity for poor people to raise their revenues. Financial inclusion is fundamental for building a comprehensive money-related financial system as well as the overall inclusive economy of the Nation and it will be provided by financial institutions like banks, co-operatives, finance, etc. Among them, this study has been focused on the Satyeta Saving and Credit Co-operative, located in Pokhara 26 Kaski, with the objectives: to explore the proportion of financial inclusion of women caste-wise, to measure the services provided by the cooperative to promote investment and enterprises, to analyze the financial eminence of the women afterwards involvement in the co-operative and to analyze the societal prestige of the women after connection in the co-operative. This study mainly concentrated on women because women are being differentiated against in every aspect of society. Many reasons strapped women to the back of the development. In this co-operative, there are 628 members among them 324 are female which is the population of this study and out of them, 90 were nominated as a sample of this study, exhausting a simple random sampling method, selected by lottery method. By means of a questionnaire the data were composed and contingent applying statistical tools like mean, percentage, etc. This study catches that the cooperative has no methods to the Dalits and back-warded women so less number of Dalits women was convoluted in this cooperative. Young and married women were intricate in these co-operatives from the initial date but they were involved for the bonus rather than enterprises and business. The women have accounts in others banks and they essential facilities like ATMs and other services which will not deliver by the cooperative. The existence of this cooperative in financial inclusion seems dispossessed, although the economic and social pointers of the women are not in a decreasing situation. Finally, women were busy in other banks and financial institutions so the changes arising due to other banks or particularly from this cooperative are problematic to recognize which is the limitation of this study. Where a single financial institution runs, and service delivered by the institution is to be dignified to mark the study more critical in a remote area.